Estimation of the burden of human placental micro- and nano-vesicles extruded into the maternal blood from 8 to 12 weeks of gestation. (December 2018) - Liu, Haiyan; Kang, Matt; Wang, Julie; Blenkiron, Cherie; Lee, Arier; Wise, Michelle; Chamley, Larry; Chen, Qi
Abstract: Background: The human placenta extrudes a variety of extracellular vesicles (EVs) into the maternal blood daily. These vesicles may be crucial to the adaptation of the maternal cardiovascular and immune systems to pregnancy. Quantifying the EVs that are released in early gestation is important to our understanding of how placental EVs may contribute to the regulation of maternal physiology. Methods: EVs were isolated from first trimester placental explants and separated into micro- and nano-vesicles by differential centrifugation. The numbers of each type of EVs extruded from each milligram of placentae between gestational weeks 8 and 12 was determined by Nanoparticle Tracking Analysis. The total protein or DNA content of the vesicles was determined by BCA assay or Qubit ® 2.0. Results: Neither the number of micro- nor nano-EVs/mg explant (n = 49), nor the total protein (n = 19) and DNA content (n = 29) of these EVs changed significantly between 8 and 12 weeks of gestation. When the increasing placental weight with gestation was accounted for, the daily number of placental EVs extruded into the maternal blood increased by more than 100 fold between 8 and 12 weeks (micro-EVs 6.23 X 10 14 and nano-EVs 1.84 X 10 14  at 12 weeks, p = 0.0003). Discussion: Constant production of micro- and nano-EVs per-milligram placenta, regardless of gestational age, and the increased daily burden of EVs across gestational age indicate these EVs have the potential to regulate maternal physiology from early pregnancy. Since total EV protein content, like EV numbers was, constant, this is a potentially reliable surrogate for quantifying EVs. Highlights: The amount of extracellular vesicles/mg placenta unchanged in first trimester. Over 100 fold of placental extracellular vesicles increase in 12 weeks. The protein levels of extracellular vesicles unchanged across in first trimester. The measurement of DNA levels in extracellular vesicles is more variable.